Architectural Engineering Design: Structural Systems - Brown Butler Robert (MC Graw Hill, 2002)
Architectural Engineering Design: Mechanical and Structural Systems provide the architectural and design professions a comprehensive, definitive reference to more than 1100 equations essential to all aspects of building design and construction. Calculations books have been successful in all the engineering disciplines, and there is nothing even remotely comparable on the market for architects-until now.